Usage of Foods for Special Medical Purposes in the Pediatric Ward Dr. Soetomo Hospital Surabaya - Dwi Lestari Avianti; Nur Aisiyah Widjaja; Roedi Irawan (Humanistic Network for Science and Technology (HNST), 2020)
Children who are hospitalized are at risk of malnutrition due to increased energy requirements caused by underlying disease, drug use, decreased appetite and inadequate diet during treatment which can inhibit growth and development. Medical nutrition is required to use food for special medical purposes (FSMP) to meet nutritional needs during hospitalization. The aim of this study is to know the number of patients and types of medical indications for FSMP administration. This research was conducted from August 2018 to October 2018 by reviewing the medical records of children who were treated in the pediatric ward Dr. Soetomo Surabaya. The inclusion criteria were children aged 1 month -18 years and received FSMP as indicated. The sampling method is total sampling. Data in the form of age, gender, nutritional status, disease diagnosis and FSMP type administration, were obtained from medical records from April 2017 to April 2018. The samples obtained were grouped according to indications for FSMP use based on the pediatric drug dosage book of the Indonesian Pediatric Association. A total of 402 children were enrolled in this study. Male patients who received FSMP were 229 (56.9%). The highest use of FSMP was at the age of less than 1 year as many as 195 patients (48.5%) with the highest indication of malnutrition. The most indications for FSMP are malnutrition as many as 267 patients (66.4%), which was caused by gastrointestinal (GI) disease (24.4%), malignancy (18.4%) and congenital heart disease (CHD) (11.2%). The second highest indication of FSMP was malabsorption in 210 patients (52.2%), caused by gastrointestinal disease (41.4%) and cholestasis (17.6%). Another indication that there was volume limitation in 51 patients (12.7%), mostly due to CHD accompanied by heart failure and cow's milk protein allergy (CMPA) in 38 patients (9.5%), more with gastrointestinal symptoms (60.5%) than respiratory symptoms (39.5%). The use of FSMP in the pediatric ward Dr. Soetomo Hospital, Surabaya with medical indications of malnutrition (moderate malnutrition, severe malnutrition, failure to thrive), malabsorption, volume limitation and cow's milk protein allergy with malnutrition as the most indications. Keywords: hospitalized children; medical nutrition; foods for special medical purposes; nutritional requirements